PELATIHAN: METODE VALUE PROPOSITION DALAM UPAYA MENJAGA KEBERLANGSUNGAN BISNIS HOME INDUSTRY DI CIKAMPEK - Edi Susanto; Hari Adianto; Arief Irfan Syah Tjaja; Ghifari Hamzah; Rara Massayu Sabila Salma Susanto (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This activity provides an understanding of the value proposition (VP) method to 13 home industry players in Cikampek. The training is performed comprehensively with a value proposition approach, as a business continuity effort, where the actors in this partner are facing problems with the impact of the pandemic; business difficulties, lack of knowledge and innovation in managing, lack of understanding of capital and finance. The training needs performed the materials needed for this home industry business, such as; business management and innovation, financial report preparation, and value proposition approach strategy, which includes 8 elements; product design, raw materials, packaging, features, process, distribution, service, price. The methodology used is blended learning, namely offline and online, due to the current pandemic situation, offline participants are limited to only 5 people with strict health protocol rules (wearing masks, hand sanitizer, checking temperature, washing hands, and towels), the rest is online. via zoom meeting. Evaluation of this training is performed by conducting a pretest before the event starts and a post-test at the end of the activity after the assignment. The evaluation results from this training were declared successful because each participant was judged to be able to understand the material delivered with the average overall assessment result meeting the success standards set with good results.